MENINGKATKAN KEMAMPUAN INTELEKTUAL ANAK USIA DINI MELALUI PERMAINAN DOMINO STIK PADA KELOMPOK B DI TK TRIALINGGA KINDERSCHOOL KOTA CIMAHI - Neni Melawati; Tresnawulan Tresnawulan (IKIP Siliwangi, 2018)
Early childhood education is an effort to stimulate, guide, nurture and provide learning activities that will result in the abilities and skills of the child. Early childhood education is an education done in newborn children up to eight years old. Education at this stage focuses on physica, intelligence / cognitive, emotional and social education .. Cognitive ability is one of the abilities that must be developed in early childhood. Through this domino sticks are expected to be a fun means so as to attract interest in playing and learning as well. Cognitive or intellectual is a process of thinking in the form of ability or power to connect another event and the ability to assess and considereverything observed from the data around. Important processes in children's cognitive development include assimilation schemes, accommodation, organization, balance and balancing. In this game has the purpose of which is the child can classify objects based on the shape of color or size can understand the rules in a game understand and do the rules of the game disentra, can recognize geometric shapes. With the game domino sticks children can develop the power of thinking, creativity and improve the cognitive development of children